Mechanism and effects of STING–IFN-I pathway on nociception: A narrative review - Yang, Jinghan; Ding, Hui; Shuai, Bo; Zhang, Yan; Zhang, Yan (Frontiers in Molecular Neuroscience, 2023)
Since the discovery of STING in 2008, numerous studies have investigated its functions in immunity, inflammation, and cancer. STING activates downstream molecules including IFN-I, NLRP3, and NF-κB. The STING–IFN-I pathway plays a vital role in nociception. After receiving the upstream signal, STING is activated and induces the expression of IFN-I, and after paracrine and autocrine signaling, IFN-I binds to IFN receptors. Subsequently, the activity of ion channels is inhibited by TYK2, which induces an acute antinociceptive effect. JAK activates PIK3 and MAPK–MNK–eIF4E pathways, which sensitize nociceptors in the peripheral nervous system. In the mid-late stage, the STING–IFN-I pathway activates STAT, increases pro-inflammatory and anti-inflammatory cytokines, inhibits ER-phagy, and promotes microglial M1-polarization in the central nervous system, leading to central sensitization. Thus, the STING–IFN-I pathway may exert complex effects on nociception at various stages, and these effects require further comprehensive elucidation. Therefore, in this review, we systematically summarized the mechanisms of the STING–IFN-I pathway and discussed its function in nociception.